Etiological factors of chronic renal failure - Mirazimova Nozima (KLINIK VA FUNDAMENTAL TIBBIYOT TADQIQOTLARI JURNALI, 2026)
The global trajectory of chronic renal failure is escalating, driven by demographic aging and the expansion of metabolic syndromes. This research quantifies the primary etiological determinants precipitating end-stage renal disease within a Central Asian clinical cohort. Using a retrospective, longitudinal design, we analyzed diagnostic registries of 1,452 adult patients with Stage III to V chronic kidney disease between 2022 and 2026. Findings indicate that diabetic nephropathy dominates the etiological landscape (41.6%), followed closely by hypertensive nephrosclerosis (35.2%). Primary glomerulonephritis accounts for only 11.4%. Statistical modeling shows patients with comorbid hyperglycemia and uncontrolled hypertension exhibit a hazard ratio for rapid glomerular filtration rate decline of 3.82 (95% CI: 3.15 - 4.60, p < 0.001). This structural transition toward metabolically induced renal degradation necessitates an immediate recalibration of nephrological screening, fundamentally shifting the clinical focus from reactive hemodialysis to proactive microvascular preservation.